2014
DOI: 10.1177/0961203314555537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity on health-related quality of life in juvenile-onset systemic lupus erythematosus

Abstract: Objective Evaluate the effects of obesity on health-related quality of life (HRQOL) measures in juvenile-onset SLE (jSLE). Methods Obesity was defined as a body mass index (BMI) ≥ 95th% according to the sex-specific Center for Disease Control body mass index-for-age charts and determined in a multicenter cohort of jSLE patients. In this secondary analysis, the domain and summary scores of the Pediatric Quality of Life (PedsQL) Inventory and the Child Health Questionnaire (CHQ) of obese jSLE patients were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 13 publications
2
14
0
2
Order By: Relevance
“…Interestingly, an even larger negative effect was seen with regard to factors affecting physical appearance. Indeed, 2 other studies showed that changes in physical appearance (e.g., obesity, skin involvement) were associated with reduced HRQoL . Surprisingly, in the CHILL‐NL cohort, the presence of damage barely affected HRQoL, with only scores in the physical functioning domain significantly reduced.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, an even larger negative effect was seen with regard to factors affecting physical appearance. Indeed, 2 other studies showed that changes in physical appearance (e.g., obesity, skin involvement) were associated with reduced HRQoL . Surprisingly, in the CHILL‐NL cohort, the presence of damage barely affected HRQoL, with only scores in the physical functioning domain significantly reduced.…”
Section: Discussionmentioning
confidence: 91%
“…This measure has not been used as an outcome measure in clinical trials, but it has been used as an outcome measure in a number of observational studies (6,42–44). For example, a study of 98 children with cSLE demonstrated significantly lower HRQoL in children with cSLE compared with normative cohorts, including a mean CHQ PhS of 49 (SD 7) and a mean CHQ PsS of 42 (SD 12) (5).…”
Section: Child Health Questionnairementioning
confidence: 99%
“…No obstante, diversos factores medioambientales como la exposición a tóxicos, a fármacos, el tabaquismo y factores hormonales entre otros han sido ampliamente investigados y relacionados con el LES, por lo que no es de extrañar que la obesidad tenga también un papel en la patogénesis del LES. Donde sí parece existir evidencia es en la relación que existe entre la obesidad y peores índices de funcionalidad y calidad de vida en pacientes con LES [41,42] .…”
Section: -Resistinaunclassified